TAHAP-TAHAPAN PEMBUATAN PETA TATA GUNA LAHAN KECAMATAN KALIDONI - Diki Bahrih, Mohamad Rezeki; Rosyad, Farlin (Ensiklopedia Research and Community Service Review, 2025)
The main purpose of this study is to examine in depth and document in detail each stage involved in the process of making land use maps in the Kalidoni District area. Land use maps have a very important role as one of the main components in regional planning activities and strategic decision-making related to regional development. This study uses a systematic and structured approach to identify, analyze, and explain in detail each step in the entire process of making the land use map.Keywords: Land use map, Kalidoni District, Regional planning, Regional development, Systematic approach, Spatial mapping